Baggage [large type] : tales from a fully packed life - Cumming, Alan, 1965- (Harper Large Print, 2021)
"With the release of his first memoir, Not My Father's Son, Alan Cumming felt the power that came with sharing his truth. Shocking fans and readers with the reality of his childhood trauma, Not My Father's Son was a #1 New York Times bestseller and universally landed for its searing honesty and the way in which Alan relentlessly sought answers to questions about his family and his past. And, as an added and perhaps unexpected benefit, he inspired others to engage with their own sources of pain. Alan found that his words were powerful, that his authenticity was a clarion call. But behind the fun-loving, happy persona is the truth of Alan's life, a truth he shares in Baggage. The message that comes through time and time again in this wise and witty second memoir is that the past is not something to forget or 'get over.' Alan hasn't miraculously healed from the trauma of his father's abuse. His life today is one where he artfully manages what happened to him, even as it still haunts. In a series of episodes that are bookended by two marriages, the ending of his first to his wife, and the start of his second to his husband, Baggage charts Alan's unique and wonderful career onstage and onscreen and all the times that Hollywood has, since his nervous breakdown at the age of twenty-eight, swooped into his life to whisk him away from all sorts of calamity or moments of personal destruction. Populated by marquee names (Liza! Faye Dunaway! Gore Vidal! X-Men! Kubrick! The Spice Girls!) and moments of hilarity, heartbreak, bad decisions, bold moves, but always authenticity, Alan Cumming reveals himself as entirely human -- a happy, flawed, vulnerable, fearless middle-aged man, with a lot of baggage. An entertaining, but entirely thoughtful, memoir of a man who embraces both the darkness and the light, Baggage is a true delight from start to finish." --